Design of Geopolymers Based on Greek CDWs Using the Taguchi Method - Dimitrios Kioupis (Eng)
This study explored an alternative approach to managing construction and demolition waste (CDW) in Greece by repurposing waste bricks and tiles as secondary raw materials for geopolymer synthesis. Alkali dissolution tests indicated that waste brick is more susceptible to alkaline attack than tile waste. The Taguchi method was employed as a design of experiments (DoE) approach to optimize synthesis and address CDW mineralogical variability, targeting maximum compressive strength. The primary influencing factors were alkali content (64%) and soluble silicon (33%). Geopolymers with a compressive strength of 42.8 MPa were synthesized at 90 °C for 3 days under optimal conditions: a soluble silicon-to-alkali molar ratio of 0.5, an alkali-to-aluminum molar ratio of 1, and a 50:50 sodium–potassium ion mixture.